Student-driven differentiation : 8 steps to harmonize learning in the classroom - Westman, Lisa (Corwin, 2018)
Full of just-in-time, step-by-step guidance, this book shows you how to incorporate student voice and choice in the process of planning for student-driven differentiation. This unique approach is based on building collaborative student-teacher relationships as a precursor to student growth.